Answer:
3x^2−8x−3
Step-by-step explanation:
(3x+1)(x−3)
=(3x+1)(x+−3)
=(3x)(x)+(3x)(−3)+(1)(x)+(1)(−3)
=3x^2−9x+x−3
=3x^2−8x−3
Answer:
When you move down you subtract and when you move to the right you subtract when your moving up or to the left you add. hope that helped :-)
Step-by-step explanation:
Answer:
6x+2
Step-by-step explanation:
your combine like terms...
so 13x is teh same as -7x
13x-7x= 6x
3 and -1 are the same as well
3-1=2
so teh answer would be
6x+2
The answer is y=10/7-5/7x, subtract the 5x and put it on the other side then divide the 7 from the y and divide it to 10-5x to get the answer.